2013
DOI: 10.4236/mrc.2013.23012
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneously Catalyzed Transesterification of Nigerian <i>Jatropha curcas</i> Oil into Biodiesel: A Kinetic Study

Abstract: As a follow-up to our previous study on the transesterification of Nigerian Jatropha curcas oil into Biodiesel using homogenous catalysis, kinetic study of the reaction is hereby presented. The kinetic study revealed that the rate of formation of biodiesel can be increased by increasing reaction temperature and oil to alcohol molar ratio. The optimum reaction condition was established to be 60˚C (reaction temperature) and 1:6 (oil to alcohol ratio). Accordingly, the highest biodiesel yield obtained from homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The estimated reaction rate constant, k 1 = 0.0059 ± 0.0002 L mol −1 min −1 , was in the similar range as reported by Aransiola et al [38]. Figure 9 suggested that this model was a reasonable fit (correlation of coefficient = 0.865) to the data of the initial reaction period (0-20 min).…”
supporting
confidence: 83%
“…The estimated reaction rate constant, k 1 = 0.0059 ± 0.0002 L mol −1 min −1 , was in the similar range as reported by Aransiola et al [38]. Figure 9 suggested that this model was a reasonable fit (correlation of coefficient = 0.865) to the data of the initial reaction period (0-20 min).…”
supporting
confidence: 83%
“…Many researchers studied transesterification reactions kinetics intensively [44][45][46]. The main concern of these studies is to obtain a reasonable reaction rate expression in order to have a proper design for a reactor its aim is the production of biodiesel.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…Experimental results provided in Table 3 were employed in developing a regression model using the general polynomial regression model presented in Eq. (2) (5) where T, t and W are the reaction temperature ( • C), the reaction time (min) and the catalyst weight (in wt.%), respectively. The experimental yield of biodiesel (Y e ) was also compared with the predicted biodiesel yield (Y p ) as shown in Table 3.…”
Section: Empirical Modelling and Influence Of Operating Variablesmentioning
confidence: 99%
“…These raw materials are not entirely suitable, more especially in developing countries, due to the limited supply and high cost associated with their application, as well as competition with the food chain [2]. Therefore, low cost, non-edible oils such as jatropha oil, animal fat and waste cooking oil have been suggested and tested as alternatives [3][4][5]. However, the main disadvantage of these non-edible types of feedstock is the high content of free fatty acid (FFA) within the oils, which poses problems in the production process.…”
Section: Introductionmentioning
confidence: 99%